Effect of Fumigation with 1, 3-Dichloropropene and Chloropicrin on Fomesafen Dissipation in Eggplant Plasticulture Production. Issue 2 (9th October 2017) - Reed, Thomas V.; Boyd, Nathan S.; Wilson, P. Christopher; Dittmar, Peter J.
Abstract : Fomesafen is a protoporphyrinogen oxidase (PROTOX) inhibitor that has the potential to be used as an alternative mechanism of action for PRE nutsedge and broadleaf weed control in Florida production of small fruit and vegetables. Fumigation in the raised-bed plasticulture system may increase herbicide persistence. Fomesafen persistence could dissuade Florida growers from using the herbicide for fear of injury to subsequent susceptible crops. Field experiments were conducted in Balm, FL, in 2015 and 2016 to investigate the effect of fumigation on fomesafen dissipation, eggplant tolerance, and purple nutsedge control. Treatments included fomesafen at 0.42 kg ai ha −1, S -metolachlor at 1.06 kg ai ha −1, and a nontreated control in either a fumigated bed injected with a combination of 39% 1, 3-dichloropropene and 59.6% chloropicrin at 336 kg ha −1 or no fumigant. Fomesafen concentration in the soil decreased by 83% and 96% from application to harvest in 2015 and 2016, respectively. Fumigation did not affect fomesafen dissipation in either year. At 2 wk after transplant (WATr), fomesafen caused 14% eggplant injury. Injury decreased to less than 5% at 6 WATr. Fomesafen and S -metolachlor treatments did not reduce eggplant height or yields compared with the nontreated control. Fumigation and fomesafen did not decrease purple nutsedge density; however, S -metolachlor applications resulted in a 48% reduction. Further research is needed to assess efficacy on broadleaf and grass weeds.